Transfer Pricing, Kompensasi Rugi Fiskal, Financial Distress dan Agresivitas Pajak - Iswatini, Nisa; Asalam, Ardan Gani (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to analyze the effect of transfer pricing, fiscal loss compensation, and financial distress on tax aggressiveness in mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. The research population uses 54 mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection used purposive sampling technique, in order to obtain 14 samples with a total sample of 70 for the 5 year study period. The analysis technique used is panel data regression with the use of Eviews 12 in processing the data. Based on the results of the study, it was found that financial distress had a positive effect on tax aggressiveness, while transfer pricing and fiscal loss compensation had no effect on tax aggressiveness. Keywords: Tax Aggressiveness; Transfer Pricing; Fiscal Loss Compensation; Financial Distress.